The Prevalence and Correlates of Suicidal Ideation among University Students : A Survey - Jun Choi, Lee; Mazz Adriz Fadzillah, Mazelan (UNIMAS Publisher, 2022)
This study aims to determine the frequency and correlates of suicidal thoughts among students who are studying at a public university in Malaysia. A convenience sample strategy was used to recruit 371 undergraduate students for this survey research project. The respondents' information was analysed using descriptive and inferential statistics. According to the findings, a significant number of respondents scored positive for the emergence of suicidal ideation. The study also suggests that there is a strong link between suicidal thoughts, depression, and anxiety in this study. However, there is no notable link between suicidal ideation and substance use.